Shared binding sites for the Bacillus thuringiensis proteins Cry3Bb, Cry3Ca and Cry7Aa in the African sweetpotato pest Cylas puncticollis (Brentidae) - Hernández Martinez, P.; Vera Velasco, N.M.; Martínez Solis, M.; Ghislain, M.; Ferre, J.; Escriche, B. (American Society for Microbiology, 2014)
Bacillus thuringiensis Cry3Bb, Cry3Ca, and Cry7Aa have been reported to be toxic against larvae of the genus Cylas , which are important pests of sweet potato worldwide and particularly in sub-Saharan Africa. However, relatively little is known about the processing and binding interactions of these coleopteran-specific Cry proteins. The aim of the present study was to determine whether Cry3Bb, Cry3Ca, and Cry7Aa proteins have shared binding sites in Cylas puncticollis to orient the pest resistance strategy by genetic transformation. Interestingly, processing of the 129-kDa Cry7Aa protoxin using commercial trypsin or chymotrypsin rendered two fragments of about 70 kDa and 65 kDa. N-terminal sequencing of the trypsin-activated Cry7Aa fragments revealed that processing occurs at Glu 47 for the 70-kDa form or Ile 88 for the 65-kDa form. Homologous binding assays showed specific binding of the two Cry3 proteins and the 65-kDa Cry7Aa fragment to brush border membrane vesicles (BBMV) from C. puncticollis larvae. The 70-kDa fragment did not bind to BBMV. Heterologous-competition assays showed that Cry3Bb, Cry3Ca, and Cry7Aa (65-kDa fragment) competed for the same binding sites. Hence, our results suggest that pest resistance mediated by the alteration of a shared Cry receptor binding site might render all three Cry toxins ineffective.